PENERAPAN LAB VIRTUAL DENGAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN ABAD 21 PADA SISWA SMP - Rahmi Hidayatul Lisma; Prima Aswirna; Hurriyah Hurriyah (UIN Imam Bonjol Padang, 2021)
This research is motivated by the learning model applied by educators is less varied and impossible to use laboratories for learning during the current pandemic, resulting in the low skills of 21st century students. To improve that, they can apply a virtual lab with a guided inquiry model with a learning home portal. This study aims to determine the 21st century skills of students. This type of research is a quasi-experimental research, with a randomized posttest control qroup only design. The population was class VIII students which consisted of 6 classes. The sampling technique used is cluster random sampling. The results of this study indicate that the average student learning outcomes in the final test of the experimental class is 85.92 and in the control class is 43.33 on both learning materials. between 21st century skills class VIII 5 and VIII 6 that t count > t table; 11,579 > 2,06390 means Ha is accepted, Ho is rejected. In conclusion, students' 21st century skills by applying a virtual lab with a guided inquiry model assisted by a learning home portal are better than applying conventional learning models in class VIII of SMPN 1 Ulakan Tapakis